ARAHAN PENATAAN PEDAGANG KAKI LIMA (PKL) DI KAWASAN SEKITAR PASAR ATRIUM PONDOK GEDE (APG) - Sutaryo Sutaryo; Fadillah Rizki Putra (Jurnal Ilmiah Plano Krisna, 2024)
This study discusses the arrangement of street vendors (PKL) around Atrium Pondok Gede Market (APG), Bekasi. The main problems include a strategic location that triggers congestion, limited business space causing vendors to sell on sidewalks and roads, weak supervision, traffic jams, disturbances for pedestrians, and declining urban spatial quality. The aim of the study is to formulate directives for organizing street vendors using GIS analysis methods, qualitative-quantitative approaches, and SWOT. The results show that the presence of street vendors is not in accordance with spatial planning or existing regulations. The arrangement directives include grouping types of merchandise, providing infrastructure and green open spaces, organizing pedestrian pathways, drainage, regulating operating hours, and relocating vendors. The main strategy (SO) emphasizes collaboration among stakeholders, improving accessibility, providing facilities, and fostering street vendors as part of MSMEs